Association of caffeine intake with all-cause and cardiovascular mortality in elderly patients with hypertension - Chen, Shuaijie; Li, Jing; Gao, Menghan; Li, Duanbin; Shen, Ruming; Lyu, Lingchun; Shen, Jiayi; Shen, Xiaohua; Fu, Guosheng; Wei, Tiemin; Zhang, Wenbin (Frontiers in Nutrition, 2022)
Background Caffeine is widely consumed not only in coffee but also in soft drinks and tea. However, the long-term health effects of caffeine are still controversial, especially in people with high cardiovascular risk such as elderly patients with hypertension. Methods This study analyzed data from the National Health and Nutrition Examination Survey 2003–2018. Caffeine intake was calculated by two 24-h dietary recall interviews. Complex sampling-weighted multivariable Cox proportional hazards models were used to compare the hazard ratios (HRs) of all-cause and cardiovascular mortality in elderly hypertensive patients with different caffeine intake (<10, 10 to <100, 100 to <200, 200 to <300, and ≥300 mg/day). Results This study included 6,076 elderly hypertensive patients. The mean ± standard error follow-up duration was 6.86 ± 0.12 years. During this period, a total of 2,200 all-cause deaths occurred, of which 765 were cardiovascular deaths. Taking patients with caffeine intake < 10 mg/day as a reference, patients with moderate caffeine intake (200 to <300 mg/day) had a lower risk of all-cause (HR, 0.70 [95% CI, 0.56–0.87]) and cardiovascular (HR, 0.55 [95% CI, 0.39–0.77]) mortality. The benefit of reducing all-cause mortality risk was significant in female patients (HR, 0.65 [95% CI, 0.50–0.85]) or patients with well-controlled blood pressure (HR, 0.63 [95% CI, 0.46–0.87]), but not in male patients or patients with poorly controlled blood pressure. In addition, non-linear relationship analysis also showed that moderate caffeine intake had the lowest HRs of all-cause (Non-linear p = 0.022) and cardiovascular mortality (Non-linear p = 0.032) in the present study. Conclusion Moderate caffeine intake is associated with reduced risk of all-cause and cardiovascular mortality in elderly hypertensive patients.